INTEGRASI FILSAFAT ILMU DALAM PENGEMBANGAN TEORI PERILAKU ORGANISASI BERBASIS NILAI DAN MORAL - Ningrum, Dhea Agusty; Siagian, Tomy Sun; Mujiatun, Siti (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Organizational behavior studies have long been dominated by positivistic and rational-economic paradigms that position humans as instrumental actors. Such domination has marginalized moral and ethical dimensions in organizational practices, leading to increasing ethical violations, leadership crises, and declining organizational legitimacy. This study aims to examine the role of philosophy of science as the foundation for developing value- and morality-based organizational behavior theory. A qualitative approach was employed through a critical literature review of scientific publications related to philosophy of science, management, and organizational behavior. The findings indicate that integrating ontological, epistemological, and axiological dimensions enables the repositioning of humans as moral subjects, expands epistemological approaches through interpretive–reflective methods, and reinforces the normative purpose of organizational behavior science. This study concludes that value- and morality-based organizational behavior theory is essential for building ethical, just, and sustainable organizations, particularly within the Indonesian socio-cultural context